2023
DOI: 10.3390/su15097641
|View full text |Cite
|
Sign up to set email alerts
|

Climate Mitigation Strategies: The Use of Cool Pavements

Martina Giorio,
Rossana Paparella

Abstract: Recent statistical reports highlight an accelerating phenomenon of radical urbanization, and the forecasts estimate that within the next ten years, about 70% of the world’s population will be located in urban areas, compared with 54% currently living there. This phenomenon will result in an increase in the constructed volume, with foreseeable adverse effects on the climate, the environment, and residents’ health. The resulting growth of the emissions and the use of energy resources, combined with changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…Considering the evaluation of the given renovation plan, through employing the CFD approach, it was found (see Tables 5 and 6) that the proposed plan not only retains low UHI intensities within the urban squares but also reduces heat stresses in the perimetric roads. Indicatively, the temporally maximum mean surface temperature is reduced by around 10 • C at the exposed perimetric roads due to the use of more reflective materials, similar to the findings of the assessment of cool materials' impacts in Greece [4], Italy [22] and Albania [14]. The slight increase in the surface temperature in some non-shaded parcels of the Liberty Square due to the less-reflective travertine marble is compensated for by the new green and blue measures, i.e., more trees, grass beds (well irrigated) and a big fountain.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Considering the evaluation of the given renovation plan, through employing the CFD approach, it was found (see Tables 5 and 6) that the proposed plan not only retains low UHI intensities within the urban squares but also reduces heat stresses in the perimetric roads. Indicatively, the temporally maximum mean surface temperature is reduced by around 10 • C at the exposed perimetric roads due to the use of more reflective materials, similar to the findings of the assessment of cool materials' impacts in Greece [4], Italy [22] and Albania [14]. The slight increase in the surface temperature in some non-shaded parcels of the Liberty Square due to the less-reflective travertine marble is compensated for by the new green and blue measures, i.e., more trees, grass beds (well irrigated) and a big fountain.…”
Section: Discussionsupporting
confidence: 74%
“…[16]. Based on its advantage of containing special urban physical models (e.g., evaporation from water surfaces, evapotranspiration from vegetation, basic turbulence modelling and thermal comfort indices) relieving the user of own-defined functions and codes, the ENVI-met software has been extensively used in urban planning studies, mainly for exploring the impacts of alternative design scenarios [18][19][20][21][22], urban configurations and morphologies [23,24] and novel artificial materials such as supercool materials [25] or nature-based solutions [19,26,27]. On the other hand, taking into account its flexibility in coupling with zonal models for assessing urban microclimate effects on building energy performance [16,28], but especially due to its numerous alternatives regarding grid meshing in complex geometries and turbulence modelling [16], the Ansys FLUENT software has gained popularity in advanced urban planning studies.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis to evaluate the effects of various urban features on microclimate was based on simulations of the urban microclimate using ENVI-met software (v 5.5.1, ENVImet, GmbH, Essen, Germany), a computational fluid dynamics software that has been used and tested widely [44][45][46][47][48][49][50][51][52][53], especially in Asia [53,54]. Studies have shown that, for the ENVImet model setting, the model provides the best performance by fully forcing meteorological boundary conditions and localizing the material.…”
Section: Meteorological Data Recordmentioning
confidence: 99%
“…Giorio et al [39] carried out a study related to the city of Padua in Italy; the main outcomes revealed that cool pavement surfaces were cooler by up to 9 • C in the central hours, reducing air temperatures by 0.6 to 1.2 • C, at the pedestrian level. It confirms the possibility of using such materials as a mitigation measure.…”
Section: Introductionmentioning
confidence: 99%